Short-Term Efficacy of Autologous Cellular Micrografts in Male and Female Androgenetic Alopecia: A Retrospective Cohort Study - Zari S (Dove Medical Press, 2021)
Shadi Zari Department of Dermatology, Faculty of Medicine, University of Jeddah, Jeddah, Saudi ArabiaCorrespondence: Shadi Zari Email shadizarimd@gmail.comPurpose: Autologous cellular micrografts (ACM) is a novel treatment method in hair loss, and few data are available regarding its efficacy. The present study was carried out to assess the short-term clinical efficacy of a single application of ACM in the treatment of male and female androgenetic alopecia (AGA).Materials and Methods: This was a single-center retrospective study involving 140 consecutive adults with confirmed AGA, who received a single session of ACM (Regenera Activa®). Efficacy was evaluated 1- 6 months after treatment, by analyzing the change of trichometry parameters, which were assessed using TrichoScan digital image analysis.Results: Depending on the scalp region, there was increase in mean hair density by 4.5- 7.12 hair/cm2, average hair thickness by 0.96- 1.88 μm, % thick hair by 1.74- 3.26%, and mean number of follicular units by 1.30- 2.77, resulting in an increase of cumulative hair thickness by 0.48- 0.56 unit. Additionally, the frontal region showed a significant decrease in % thin hair (− 1.81%, p = 0.037) and yellow dots (− 1.93 N/cm2, p = 0.003). A favorable response was observed in 66.4% of the participants in the frontal region. Further, a gender-specific effect of treatment was observed.Conclusion: ACM is a promising treatment in AGA with a short-term favorable response observed in up to approximately two-thirds of patients.Keywords: androgenetic alopecia, pattern hair loss, autologous cellular micrografts, efficacy, regrowth